2007
DOI: 10.1111/j.1537-2995.2007.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi–Chinese blood center study testing serologic‐negative donor samples for hepatitis C virus and human immunodeficiency virus with nucleic acid testing

Abstract: The residual risk for transfusion-transmitted HCV infection is still relatively high in China. Incorporating NAT technology into blood donor screening would be estimated to reduce the residual risk of HCV infections eightfold over current EIA screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
0
26
1
Order By: Relevance
“…The average newly acquired HCV rate (62.8/100,000) in Yanbian Prefecture was significantly higher than the national average (8.21/100,000) and that for blood donors (24.2/100,000) [8]–[9]. It is worth nothing that the newly diagnosed rate of HCV in Yanbian Prefecture, not referred the incidence, may not accurately reflect the newly acquired HCV.…”
Section: Discussionmentioning
confidence: 99%
“…The average newly acquired HCV rate (62.8/100,000) in Yanbian Prefecture was significantly higher than the national average (8.21/100,000) and that for blood donors (24.2/100,000) [8]–[9]. It is worth nothing that the newly diagnosed rate of HCV in Yanbian Prefecture, not referred the incidence, may not accurately reflect the newly acquired HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission via transfusion was a main route of infection until 1991, but the possibility has become extremely low since a screening test was introduced for blood donors 44,45,46. The most important route of recent HCV transmission is the use of illicit drugs in developed countries such as the US or Europe; HCV prevalence rate is low,47 whereas anti-HCV prevalence in the IVDU group was reported as high as 50-90% 48.…”
Section: Preventionmentioning
confidence: 99%
“…Shan et al . [49] comparing ID NAT with pools of 16 using Procleix Duplex reagent observed that the WP extended by 2.1 days for HIV and 2.4 days for HCV for MP16. González et al .…”
Section: Comparative Evaluation Of Id Versus Mp Nat Performance With mentioning
confidence: 99%